Characterization and inhibition of interstrand crosslink repair nuclease SNM1A - Buzon, Beverly Diana (My University, 2018)
Interstrand cross-links (ICLs) are a type of DNA damage that prevents strand separation required for basic cellular processes. ICL-based anti-cancer therapies exploit the cytotoxic consequences of replication and transcription inhibition, however, they are limited by the ability of the cell to repair DNA crosslinks. The challenge of ICL repair involves coordinating multiple DNA repair pathways to remove damage occurring on both strands of DNA. Participation of factors that are both exclusive and essential to crosslink repair suggests a pathway requirement to process unique structures and/or intermediates arising only in ICL repair. SNM1A is a nuclease required for survival of human cells in response to ICL exposure, but the specific function and role of SNM1A remain unclear. Here we show that, in addition to known 5’-3’exonuclease activity, SNM1A possesses single-strand specific endonuclease activity. Furthermore, SNM1A exhibits translesion nuclease activity on crosslinks which deform the helical backbone, but not non-distorting stable ICLs. We report the identification and characterization of nine small molecules inhibitors of SNM1A, isolated from an in vitro high-throughput screen of nearly 4,000 bioactive compounds. Finally, we demonstrate that inhibitors of SNM1A potentiate the cytotoxicity of ICL-inducing agent cisplatin in HeLa cells. The work in this thesis expands the possible roles of SNM1A in ICL repair and lays the groundwork for SNM1A inhibition in ICL sensitization efforts.
Keywords: SNM1A; beta-CASP nuclease; small molecule inhibitors; translesion nuclease; chemoresistance; structure-specific endonuclease; interstrand crosslinking repair; high throughput screening